Tree Culture of Smallholder Farmers Practicing Agroforestry in Gunung Salak Valley, West Java, Indonesia - Rahman, S.A.; Sunderland, Terry C.H.; Roshetko, James M.; Basuki, I.; Healey, J.R. (Springer, 2016)
This paper investigates the types of agroforestry system that exist in Gunung Salak Valley, West Java, Indonesia in order to characterize the differences in their basic structure and associated crop plant diversity. Data were collected through rapid rural appraisal, field observation and focus groups, followed by household survey of a sample of 20 agroforestry farmers. Five main agroforestry systems (homegardens, fruit tree system, timber tree system, mixed fruit–timber system, and cropping in the forest understory) exist in the study area, and all of them exhibit a noticeable diversity in terms of both species composition and utilization. Products from farming accounted for an average 24 % of household income. They comprised agroforestry products which contributed IDR 3.25 million/year and other agricultural products contributing IDR 1.66 million/year. The observed agroforestry systems include not only a form of forest dominated by ‘cultivated trees’, but also an anthropogenic vegetation formation derived from agricultural antecedents. In land-use classifications agroforestry systems are not recognized as forestry, but like forests they provide tree products and services. Classification will always be disfunctional if a binary system is applied, thus a more sophisticated approach should be adopted that incorporates the economic and environmental characteristics of a wider range of systems.